Tra «bíos» e «zoé»: teorie femministe della biopolitica - Dini, Tristana (Annali di studi religiosi, 2006)
This essay analyzes the category of biopolitics – used by Michel Foucault to indicate the process, which began with the modern period and brought biological life to the center of politics, and was forcefully brought back into the debate by Giorgio Agamben – on the basis of feminist theories. In fact, the political meaning of the metaphysical division between qualified life and biological life and the ineludible conflict between humanity and animality reveals its full intensity a propos the difference between the sexes.